Appropriate Dynamic Channel Allocation based on Priority Scheduling in heterogeneous Cognitive Radio Networks - Tamilarasan, S; Kumar, p (International Journal of Computer Sciences and Engineering, 2025)
Cognitive Radio (CR) is an emerging wireless communication technology that offers a great solution to scarcity of radio spectrum. Cognitive Radio Network (CRN) is an intellectual wireless communication scheme that conscious of its environment. Here, problem is sensing of spectrum by heterogeneous nodes with different computing power variation, and sensing rang. There are two tasks in this networks are primary channel sensing and selection of appropriate unused channel for communication by secondary users. In this article we present an idea to formulate a contention based channel selection algorithm using priority queue scheduling algorithm. In CRN secondary users play the important role of channel selection. This algorithm will avoid collision during data transmission between heterogeneous nodes and improve the entire network throughput.